Enhanced CACIS configuration for direction of arrival estimation. Issue 19 (28th July 2022) - Zhang, Yule; Hu, Guoping; zhang, Fei; Zhou, Hao
Abstract: In this letter, an enhanced coprime array with compressed inter‐element spacing is designed for direction of arrival estimation. First, we analyse and conclude that the 0th sensor of coprime array with compressed inter‐element spacing is redundant for the consecutive lags, thus it is rearranged to the negative part to obtain enhanced coprime array with compressed inter‐element spacing. Then, on the basis of discussing the effect of the shift sensor on the difference co‐array, the number of unique lags and the range of consecutive lags are derived. Theoretical properties show that the closed‐form expressions of coprime array with compressed inter‐element spacing and enhanced coprime array with compressed inter‐element spacing are similar, while more difference lags can be generated from the latter. Moreover, larger inter‐element spacing can slightly alleviate the mutual coupling. Numerical examples verify the advantages of enhanced coprime array with compressed inter‐element spacing in direction of arrival estimation over coprime array with compressed inter‐element spacing configuration and other coprime arrays.